A companion to John Scottus Eriugena - Guiu, Adrian; Lahey, Stephen (Brill's companions to the Christian tradition ;, 2020)
John Scottus Eriugena (d. circa 877) is regarded as the most important philosopher and theologian in the Latin West from the death of Boethius until the thirteenth century. He incorporated his understanding of Latin sources, Ambrose, Augustine, Boethius and Greek sources, including the Cappadocian Fathers, Pseudo-Dionysius, and Maximus Confessor, into a metaphysics structured on Aristotle's Categories, from which he developed Christian Neoplatonist theology that continues to stimulate 21st-century theologians. This collection of essays provides an overview of the latest scholarship on various aspects of Eriugena's thought and writings, including his Irish background, his use of Greek theologians, his Scripture hermeneutics, his understanding of Aristotelian logic, Christology, and the impact he had on contemporary and later theological traditions. Contributors include: David Albertson, Joel Barstad, John Contreni, Christophe Erismann, John Gavin, Adrian Guiu, Michael Harrington, Catherine Kavanagh, A. Kijewska, Stephen Lahey, Elena Lloyd-Sidle, Bernard McGinn, Ernesto Sergio Mainoldi, Dermot Moran, Giulio D'Onofrio, Willemien Otten, and Alfred Siewers.